Barriers to and Facilitators of the Consumption of Animal-Based Protein-Rich Foods in Older Adults - Appleton, K. M. (Nutrients, 2016)
Protein intakes in the older population can be lower than recommended for good health, and while reasons for low protein intakes can be provided, little work has attempted to investigate these reasons in relation to actual intakes, and so identify those of likely greatest impact when designing interventions. Questionnaires assessing: usual consumption of meat, fish, eggs and dairy products; agreement/disagreement with reasons for the consumption/non-consumption of these foods; and several demographic and lifestyle characteristics; were sent to 1000 UK community-dwelling adults aged 65 years and over. In total, 351 returned questionnaires, representative of the UK older population for gender and age, were suitable for analysis. Different factors were important for consumption of the four food groups, but similarities were also found. These similarities likely reflect issues of particular concern to both the consumption of animal-based protein-rich foods and the consumption of these foods by older adults. Taken together, these findings suggest intakes to be explained by, and thus that strategies for increasing consumption should focus on: increasing liking/tastiness; improving convenience and the effort required for food preparation and consumption; minimizing spoilage and wastage; and improving perceptions of affordability or value for money; freshness; and the healthiness of protein-rich foods.